Probable de novo 17q duplication (q11.2-->q21.1): a newly recognised chromosomal syndrome in a child with Klinefelter's syndrome. Issue 5 (May 1993) - Butt, A M; Mehta, D; Goodeve, J A; Flinter, F A
Abstract : A child is described with a previously unreported probable trisomy for a segment of the long arm of chromosome 17 responsible for some distinct clinical features. These include craniofacial and skin abnormalities, failure to thrive, partial malrotation of the gut, malabsorption, gastro-oesophageal reflux, neurodevelopmental delay, autonomic disturbance, and cardiac and CNS abnormalities. The coexistence of Klinefelter's syndrome (47, XXY) is of minor significance in relation to this child's phenotype.